Layered manufacturing of polymer matrix composites (PMC) materials via fused deposition modeling (FDM) - Sa'ude, Nasuha (2016)
This research present the mechanical properties, Melt Flow Index (MFI) and Melt Flow Rate (MFR) of an ABS-Copper filament through the Fused Deposition Modelling (FDM) machine. The main objectives of this study are to investigate and analyze the influences of the componding ratio and process parameters of polymer matrix composite (PMC) filament wire material on the mechanical properties, melt flow index (MFI) and melt flow rate (MFR) by FDM machine. In this study, the effect MFR of 10% -40 % copper filled in 52 % - 85% % ABS filament material by volume percentage (vol. %) was investigated experimentally based on the melting temperature and feedrate with the nozzle size 0.4 mm and 0.6 mm in diameter through the FDM heated liquefied head. The mechanical properties of ABS-Copper filament through the injection molding machine and Melt Flow Rate by the FDM liquefied head was investigated in experimental for the mechanical properties and MFR. Based on the result obtained, it was found that, increment of 30 %(vol. %) copper filled in ABS filament material increase the mechanical properties and MFR (velocity and length) of PMC filament material through the FDM machine. It can be concluded that, highest temperature and feed rate are needed to extrude polymer matrix composite (PMC) filament compared to ABS filament material in FDM machine.